Improvement On Rectification And Regulation Of Power Conditioning Circuit For RF Energy Harvesting - Asli, Astrie Nurasyeila Fifie (2020)
Power management is one of critical issues in most of integrated circuit (IC) applications as it determines the ability of a device to maintain its operating time. Power management system can be divided into two parts, energy harvesting and low dropout (LDO) voltage regulator circuits. Due to the increase of radio frequency (RF) sources around the globe, RF energy harvesting system which mainly composes of a rectifier becomes promising solution to power the low-powered electronic devices as it offers low power density and smaller size of energy converter make it easily to be integrated into a chip. The sensitivity, efficiency, and output voltage play an important role in the design of rectifier for energy harvesting. High efficiency conventional rectifiers typically provide either high sensitivity or high output voltage characteristics. Due to the limitation in rectifier architectures and the physical structure of transistor that causing large voltage drop across the rectifier over a wide range of sensitivity and output voltage, improving one of the characteristics trades off the other. The objective of this research is to design a high efficiency rectifier that operates at high sensitivity, targeting urban and rural areas and producing large output voltage that is sufficient to supply low-power electronic devices. The proposed rectifier comprises bulk-to-source BTMOS differential-drive based rectifier to produce a high efficiency RF energy harvesting system. Low-pass upward matching network is applied at the rectifier input to minimize the power loss between antenna and the rectifier hence increasing the sensitivity and output voltage. Dual-oxide-thickness transistors are used in the rectifier circuit to optimize the power efficiency at each of the rectifier’s stage over a wide range of output voltage and sensitivity. The system is designed using 0.18μm Silterra RF in deep n-well process technology and produces 3.997V output at -15dBm sensitivity without the need of complex auxiliary control circuit and DC – DC charge-pump circuit. Meanwhile, technology scaling in modern IC industries causing the ripple noise from power supply become dominant for analogue and RF circuits. RF circuit demands for voltage regulator that has high power supply rejection ratio (PSRR) and low temperature coefficient as this circuit is very sensitive to noise. Small changes in its supply voltage may cause the circuit not functioning properly. Conventional regulators provide high PSRR, but it typically focuses on low frequency application. Due to this reason, LDO with high PSRR at high frequency and low temperature coefficient over a wide range of temperature is proposed. The proposed LDO uses rail-to-rail folded cascode amplifier to achieve high PSRR while obtaining good open-loop gain and stability. Large 1μF off-chip load capacitor is used to further increase the PSRR. The LDO uses transistors operating in weak and strong inversions at the voltage reference circuit to achieve 2nd order voltage-temperature characteristic hence reducing the temperature coefficient. The LDO is designed using 0.18μm Silterra thick-oxide technology and produces a constant 1.8V output voltage for input voltage between 3.2V to 5V and load current up to a 128mA at temperature between -40°C to 125°C. The LDO achieves more than 100dB PSRR for frequency greater than 900MHz and obtained temperature coefficient of lower than 5ppm/°C within the desired temperature range.